The Importance of Chemistry for Nanotechnology - Evamarie Hey-Hawkins (Syiah Kuala University, 2015)
The paradigm shift from uniform bulk materials towards nanostructured multifunctional materials is essential for future knowledge transfer from fundamental to applied sciences. In nanotechnology, two approaches are employed: “top-down” and “bottom-up”. In the top-down approach, larger assemblies are broken down to smaller units, while the bottom-up approach makes use of atomic or molecular building blocks to construct the desired nanostructures. Chemistry plays a major role in the bottom-up approach by providing progressive building blocks, such as “smart” molecules, that can be combined — preferentially by self-organisation — to create fundamentally new classes of materials. The ultimate goal is to create environmentally friendly, highly efficient, low-cost devices serving multifunctional purposes for a steadily more diversified modern society